2017
DOI: 10.1016/j.celrep.2017.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Bcl-2 by XIAP and ARTS Promotes Apoptosis

Abstract: Summary We describe a mechanism by which the anti-apoptotic B-cell lymphoma 2 (Bcl-2) protein is down-regulated to induce apoptosis. ARTS (Sept4_i2) is a tumor suppressor protein that promotes cell death through specifically antagonizing XIAP (X linked Inhibitor of Apoptosis). ARTS and Bcl-2 reside at the outer mitochondrial membrane in living cells. Upon apoptotic induction, ARTS brings XIAP and Bcl-2 into a ternary complex allowing XIAP to promote ubiquitylation and degradation of Bcl-2. ARTS binding to Bcl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 58 publications
2
78
0
Order By: Relevance
“…Recent studies have reported that ARTS can combine with BCL-2 to form a XIAP-ARTS-Bcl-2 complex. Through the E3 ubiquitin ligase function of XIAP, the complex can mediate the degradation of Bcl-2 through the ubiquitin proteasome pathway to promote apoptosis [16]. To clarify the mechanism of Septin4 in promoting the apoptosis of tumor cells, we found that Septin4 can interact with BAX and enhance this interaction following stimulation with DOX ( Figure 5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have reported that ARTS can combine with BCL-2 to form a XIAP-ARTS-Bcl-2 complex. Through the E3 ubiquitin ligase function of XIAP, the complex can mediate the degradation of Bcl-2 through the ubiquitin proteasome pathway to promote apoptosis [16]. To clarify the mechanism of Septin4 in promoting the apoptosis of tumor cells, we found that Septin4 can interact with BAX and enhance this interaction following stimulation with DOX ( Figure 5).…”
Section: Discussionmentioning
confidence: 97%
“…Septin4 is the most important XIAP antagonist proteins, located in the outer mitochondrial membrane [11][12][13][14]. When apoptosis occurs, spetin4 can translocate from the mitochondria to cytoplasm and directly bind to XIAP, thus activating caspases and leading to cell death [15,16]. Moreover, unlike traditional tumor suppressors or oncogenes, whose loss-or gain-of-function mutations can lead to the occurrence of cancer [17], Septin4 can affect tumor occurrence through expression changes, which makes it a more universal cancer suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…miR-185 regulates the Bcl-2 family to promote the sensitivity of nasopharyngeal carcinoma cells to radiation. Bcl-2 is an apoptosis-inhibiting gene, and at least 19 homologs have been discovered, which play a regulatory role in the mitochondrial-dependent apoptotic pathway and control the release of cytochrome c and other apoptotic factors in mitochondria [46,47]. Members of the Bcl-2 family contain 1-4 Bcl-2 homology domains (BH1-4), of which BH4 is a domain unique to anti-apoptotic proteins, and BH3 is a domain involved in promoting apoptosis.…”
Section: Mirnas Participate In Radiotherapy Resistance Of Nasopharyngmentioning
confidence: 99%
“…ARTS binds to p53 without affecting p53 protein stability ARTS has been documented as a key pro-apoptotic protein (Larisch et al, 2000 acting by targeting XIAP (Gottfried et al, 2004, Garrison et al, 2011 and Bcl-2 (Edison et al, 2017). Thus, we sought to explore if ARTS plays a role in p53-associated apoptotic pathway, since it is a p53-inducible gene.…”
Section: Arts Expression Is Induced By P53 In Cancer Cellsmentioning
confidence: 99%
“…ARTS initiates caspase activation upstream of mitochondria by directly binding and degrading XIAP (X-linked inhibitor of apoptosis) via the ubiquitin proteasome system (UPS) (Gottfried et al, 2004, Garrison et al, 2011. Recently, ARTS was shown to induce ubiquitination and degradation of Bcl-2 by bridging the E3-ubiquitin ligase XIAP to Bcl-2 (Edison et al, 2017). Studies in human and mice have shown that ARTS functions as a tumor suppressor protein (Elhasid et al, 2004, Kissel et al, 2005, Garcia-Fernandez et al, 2010, Fuchs et al, 2013, Koren et al, 2018.…”
Section: Introductionmentioning
confidence: 99%